Mediating Effects of Relative Handgrip Strength on the Association Between Multimorbidity and Anemia in Older Korean Adults - Jeonghyeon Kim; Taewan Kim; Yoonhwan Kim; Donghyun Kim (운동과학)
PURPOSE This study investigated the mediating effects of relative handgrip strength (RHGS) on the association between multimorbidity and anemia in older Korean adults aged ≥65 years. METHODS The data used in this study (6,900 older adults, 3,140 males, and 3,760 females) were obtained from the 2014-2019 Korean National Health and Nutrition Examination Surveys. Anemia was assessed using the World Health Organization criteria of hemoglobin levels for anemia (<13 g/dL in males and <12 g/dL in females). Chronic multimorbidity was defined as the presence of two or more chronic conditions. RHGS was evaluated using a digital hand dynamometer. The PROCESS Macro by Hayes was used to test the mediating effects of RHGS on the association between multimorbidity and hemoglobin levels. RESULTS Multivariate logistic regression revealed that individuals with ≥2 chronic conditions had significantly higher odds of anemia (odds ratio [OR]=2.425; 95% confidence interval [CI]: 1.917-3.068), and those with weak RHGS had an elevated anemia risk (OR=1.562; 95% CI: 1.339–1.821). Mediation analysis indicated that RHGS partially mediated the relationship between multimorbidity and hemoglobin levels, accounting for 19.5% of the total effect (indirect effect β=-0.0331, 95% CI: −0.0401 to −0.0265). CONCLUSIONS The findings of this study suggest that improving or maintaining handgrip strength through regular exercise is important for mitigating the risk of anemia, which can be caused by multiple chronic conditions, later in life.